Heparanase-enhanced Shedding of Syndecan-1 and Its Role in Driving Disease Pathogenesis and Progression - Rangarajan, Sunil; Richter, Jillian R.; Richter, Robert P.; Bandari, Shyam K.; Tripathi, Kaushlendra; Vlodavsky, Israel; Sanderson, Ralph D. (The journal of histochemistry and cytochemistry, 2020)
Both heparanase and syndecan-1 are known to be present and active in disease pathobiology. An important feature of syndecan-1 related to its role in pathologies is that it can be shed from the surface of cells as an intact ectodomain composed of the extracellular core protein and attached heparan sulfate and chondroitin sulfate chains. Shed syndecan-1 remains functional and impacts cell behavior both locally and distally from its cell of origin. Shedding of syndecan-1 is initiated by a variety of stimuli and accomplished predominantly by the action of matrix metalloproteinases. The accessibility of these proteases to the core protein of syndecan-1 is enhanced, and shedding facilitated, when the heparan sulfate chains of syndecan-1 have been shortened by the enzymatic activity of heparanase. Interestingly, heparanase also enhances shedding by upregulating the expression of matrix metalloproteinases. Recent studies have revealed that heparanase-induced syndecan-1 shedding contributes to the pathogenesis and progression of cancer and viral infection, as well as other septic and non-septic inflammatory states. This review discusses the heparanase/shed syndecan-1 axis in disease pathogenesis and progression, the potential of targeting this axis therapeutically, and the possibility that this axis is widespread and of influence in many diseases.